Toward Systematic Understanding of Flower Bud Induction in Apple: A Multi-Omics Approach - Milyaev, Anton; Kofler, Julian; Klaiber, Iris; Czemmel, Stefan; Pfannstiel, Jens; Flachowsky, Henryk; Stefanelli, Dario; Hanke, Magda-Viola; Wünsche, Jens-Norbert (Frontiers in Plant Science, 2021)
The induction of flower buds in apple (Malus × domestica Borkh.) is tightly connected to biennial bearing, which is characterized by alternating years with high (ON) and low or no (OFF) crop loads. In order to study this irregular cropping behavior, spur buds from ON- and OFF-trees of the biennial-bearing cultivar ‘Fuji’ and the regular bearing cultivar ‘Gala’ were collected. First, the time of flower bud initiation was precisely determined for both cultivars by histological analysis. Moreover, for a systematic understanding of flower bud induction in apple, the physiological and molecular mechanisms within the bud tissue were evaluated over four weeks prior to flower bud initiation by employing a multi-omics approach, including RNA sequencing, proteomic and metabolic profiling. Gene and protein enrichment analysis detected physiological pathways promoting and inhibiting early flower bud development. Metabolic profiles from the cropping treatments revealed a greater abundance of thiamine, chlorogenic acid, and an adenine derivative in spur buds from OFF-trees, whereas tryptophan was more abundant in the buds collected from ON-trees. Cultivar comparison indicated that chlorogenic acid was more abundant in ‘Gala’ than in ‘Fuji’ spur buds, whereas the opposite effect was found for tryptophan. Genes controlling tryptophan biosynthesis were not affected by ON- and OFF-treatments, but genes assigned to the metabolism of tryptophan into indoleacetate were differentially expressed between cultivars and treatments. The multi-omics approach permitted analyzing complex plant metabolic processes involved in early flower bud development and more specifically presumably in flower bud induction by tracing some pathways from gene to product level.